2022
DOI: 10.3390/cancers14030836
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Glioma: The Utility of Radiomic Analysis for Non-Glial Intracranial Tumors

Abstract: The field of radiomics is rapidly expanding and gaining a valuable role in neuro-oncology. The possibilities related to the use of radiomic analysis, such as distinguishing types of malignancies, predicting tumor grade, determining the presence of particular molecular markers, consistency, therapy response, and prognosis, can considerably influence decision-making in medicine in the near future. Even though the main focus of radiomic analyses has been on glial CNS tumors, studies on other intracranial tumors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…The first one is typically localized in the posterior cranial fossa and, in adults, they could develop in both hemispheres of the cerebellum, while in the pediatric age group, they are often found in the cerebellar worm [ 19 ].…”
Section: Primary Brain Tumors Hallmarks and Canonical Therapiesmentioning
confidence: 99%
“…The first one is typically localized in the posterior cranial fossa and, in adults, they could develop in both hemispheres of the cerebellum, while in the pediatric age group, they are often found in the cerebellar worm [ 19 ].…”
Section: Primary Brain Tumors Hallmarks and Canonical Therapiesmentioning
confidence: 99%
“…Numerous studies have demonstrated that radiomics exhibit superior diagnostic capabilities compared to visual analysis in the diagnosis, classification, and outcome prediction of brain lesions (Rudie et al 2019 ; Abdel Razek et al 2021 ; Forghani 2020 ; Kalasauskas et al 2022 ). Radiomics has the potential to better differentiate cerebral cystic metastases and abscesses.…”
Section: Introductionmentioning
confidence: 99%